2020
DOI: 10.3389/fpsyg.2020.584187
|View full text |Cite
|
Sign up to set email alerts
|

Does the Attentional Boost Effect Depend on the Intentionality of Encoding? Investigating the Mechanisms Underlying Memory for Visual Objects Presented at Behaviorally Relevant Moments in Time

Abstract: Pictures in a rapid serial visual presentation (RSVP) stream are better remembered when they are simultaneously presented with targets of an unrelated detection task than when they are presented with distractors. However, it is unclear whether this so-called “attentional boost effect” depends on the intentionality of encoding. While there are studies suggesting that the attentional boost effect even occurs when encoding is incidental, there are several methodological issues with these studies, which may have u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…First, target detection does not reliably increase dualtask interference for ignored background images. This was true even when ignored images were presented very briefly and/ or only one time (e.g., Yebra et al, 2019;Broitman and Swallow, 2020;Hutmacher and Kuhbandner, 2020). Second, at the least, goal-directed attention to the background item increases the magnitude of the ABE (Swallow and Jiang, 2014a;Broitman and Swallow, 2020).…”
Section: Goal-directed Attention Modulates the Effects Of Temporal Se...mentioning
confidence: 89%
See 3 more Smart Citations
“…First, target detection does not reliably increase dualtask interference for ignored background images. This was true even when ignored images were presented very briefly and/ or only one time (e.g., Yebra et al, 2019;Broitman and Swallow, 2020;Hutmacher and Kuhbandner, 2020). Second, at the least, goal-directed attention to the background item increases the magnitude of the ABE (Swallow and Jiang, 2014a;Broitman and Swallow, 2020).…”
Section: Goal-directed Attention Modulates the Effects Of Temporal Se...mentioning
confidence: 89%
“…One factor that may account for the variety of effects of target detection on incidental memory is whether the images could be attended despite instructions to ignore them. As argued by Hutmacher and Kuhbandner (2020), the presence of an ABE for incidentally presented images may depend on how long, and how many times, they are presented. When participants were instructed to memorize the objects presented in 250 ms long trials, they showed a small memory advantage (~2%) for objects that appeared with a target.…”
Section: Goal-directed Attention Modulates the Effects Of Temporal Se...mentioning
confidence: 99%
See 2 more Smart Citations
“…This is an important departure from the study reported by Mulligan et al ( 2016 ), in which participants were only instructed to remember the words. While the use of intentional instructions does not represent an essential element for obtaining the ABE (the effect has been replicated with incidental instructions: Broitman & Swallow, 2020 ; Spataro et al, 2013 ; Swallow & Jiang, 2014 ; but see Hutmacher & Kuhbandner, 2020 ), it may be instead crucial for revealing the influence of target detection on contextual memory when using verbal materials. Specifically, Broitman and Swallow ( 2020 ) showed that both recollection and familiarity estimates were greater for target-paired faces than for distractor-paired faces, regardless of whether the faces were encoded incidentally or intentionally.…”
Section: Methodsmentioning
confidence: 99%